Drug-like Inhibitors of DC-SIGN Based on a Quinolone Scaffold - Zhang, Hengxi; Daněk, Ondřej; Makarov, Dmytro; Rádl, Stanislav; Kim, Dongyoon; Ledvinka, Jiří; Vychodilová, Kristýna; Hlaváč, Jan; Lefèbre, Jonathan; Denis, Maxime; Rademacher, Christoph; Ménová, Petra (ACS medicinal chemistry letters, 2022)
DC-SIGN (dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin) is a pattern recognition receptor expressed on immune cells and involved in the recognition of carbohydrate signatures present on various pathogens, including HIV, Ebola, and SARS-CoV-2. Therefore, developing inhibitors blocking the carbohydrate-binding site of DC-SIGN could generate a valuable tool to investigate the role of this receptor in several infectious diseases. Herein, we performed a fragment-based ligand design using 4-quinolone as a scaffold. We synthesized a library of 61 compounds, performed a screening against DC-SIGN using an STD reporter assay, and validated these data using protein-based 1H-15N HSQC NMR. Based on the structure-activity relationship data, we demonstrate that ethoxycarbonyl or dimethylaminocarbonyl in position 2 or 3 is favorable for the DC-SIGN binding activity, especially in combination with fluorine, ethoxycarbonyl, or dimethylaminocarbonyl in position 7 or 8. Furthermore, we demonstrate that these quinolones can allosterically modulate the carbohydrate binding site, which offers an alternative approach toward this challenging protein target.